Pressure or Prudence? : Tales of Market Pressure and Fiscal Adjustment - Dell'Erba, Salvatore (IMF Working Papers; Working Paper ;, 2013)
We study whether multiyear fiscal adjustment plans in 17 OECD countries during 1980-2011 have been associated with market pressure. We find that only a third (34 percent) of the consolidations occurred under market pressure, suggesting that market pressure is important but not the main element associated with consolidation plans. Many adjustments under market pressure were also clustered around external shocks, and entailed larger median fiscal adjustments than other multiyear consolidations. In contrast, we find that virtually all multiyear consolidations aimed at reducing budget deficits occurred with initially weak macro-fiscal fundamentals.